Clima, cultura e teoria do Stakeholder: proposta de um plano de capacitação para o Poder Judiciário do Estado de Goiás - Chaves, Leandra Vilela Rodrigues (2019)
The objective of this study was the development of a Training Plan Proposal for the employees of the Judicial Branch of the State of Goiás, based on the identification of the main elements of organizational climate and culture, training and Stakeholder Theory, necessary for the accomplishment of the institucional mission, specially related to the agility, efficiency and effectiveness of jurisdictional activity. It was possible, through the application of the research instrument, identify sensitive areas to the demand for training and improvement actions. The importance of the study is substantiated by the evidence that continuous training actions have a positive impact on the improvement of public service, especially considering that the number of claims made by users regarding the deficiency of judicial services has generally increased. The result of the work demonstrated a strong identification of the employees with the Institution, an extremely favorable circumstance for the implementation of organizational changes, through training actions. On the other hand, the fragility in the use of technical criteria for the size of the workforce and in the definition of managerial positions has been revealed, which may compromise the achievement of the organizational objectives. The conclusion of the study is that aspects related to the behavior of employees and interpersonal relations, can not be neglected when the focus is the accomplishment of institucional mission. Also a process of evaluation of the training actions should be implemented in order to measure the effectiveness of what has been done. It is suggested, for future work, the replication of the methodology to other organs of the Judiciary and other Powers, as well as studies on the budget for training, in the context of the PJEG, in order to evaluate the efficiency of training actions, under this approach.